Push/Pull Factors, Networks and Student Migration from Côte d’Ivoire to France and Switzerland - Dago, Franck (Social Inclusion, 2021)
Since 2011, the Ivorian government has invested heavily in higher education to meet its labour market’s growing demand. In this article, we analyse the drivers of Ivorian student mobility from Côte d’Ivoire to France and Switzerland, highlighting the central role of migrant networks. We focus on the decision-making process and find that migration networks play an important role at every step: from initial aspirations to concrete plans and efforts to study abroad. Using 38 in depth interviews and two focus groups with Ivorian students who aspire to study in France and Switzerland, members of the education board, migration officers, and members of the Ivorian diaspora, we reveal that the functioning of the Ivorian higher education system is a factor of uncertainty for many students who consider that salvation can only come from migration. In addition, social representations linked to foreign diplomas inspire Ivorian students to choose international mobility. Migrant networks further encourage Ivorian students to move abroad because stories from successful migrants sharing their mobility experience are coupled with the provision of key resources to support mobility projects.